Effect of Dolomite Lime on Soil Matric Suction - M. I. S. Fazlina; Putera Agung Maha Agung; A. T. S. Azhar; Muhammad Nizam Zakaria; Mustaffa A. Ahmad; Muhammad Fathur Rouf Hasan (POLITEKNIK NEGERI JAKARTA, 2021)
The most fundamental of unsaturated soil is matric suction parameter. Matric suction in unsaturated soils plays an important role in controlling physical and mechanical properties. This parameter can influence some other important parameters of soil, such as effective stress, shear strength, swelling pressure, etc. Investigation of matric suction was performed on Ayer Hitam soil, at Batu Pahat District, Johor, Malaysia. Field monitoring works were conducted with and without dolomite treatment at the slopes of Ayer Hitam acidic soil. Field testing used some devices to find out the behavior of matric suction during the rainy session. The result shows that the soil matric suction with dolomite treatment is larger than without treatment and matric suction has a significant difference around 20 – 50 kPa. Enhancement of acidity from the dolomite treatment was not only decreasing pores size caused by the alternating of the microstructure of soil but also leading to increasing the matric suction. The treatment of dolomite material is able to control matric suction and increase the stability of slope acidic Ayer Hitam soil.